The reception of ancient Greece and Rome in children's literature : heroes and eagles - Maurice, Lisa, 1968- (Metaforms, 2015)
Greece and Rome have long featured in books for children and teens, whether through the genres of historical fiction, fantasy, mystery stories or mythological compendiums. These depictions and adaptations of the Ancient World have varied at different times, however, in accordance with changes in societies and cultures. This book investigates the varying receptions and ideological manipulations of the classical world in children's literature. Its subtitle, Heroes and Eagles , reflects the two most common ways in which this reception appears, namely in the forms of the portrayal of the Greek heroic world of classical mythology on the one hand, and of the Roman imperial presence on the other. Both of these are ideologically loaded approaches intended to educate the young reader.